Concepciones y prácticas de evaluación del aprendizaje en la Carrera de Pedagogía de la Ups Sede Quito :análisis documental de los planes de actividades de las asignaturas de las áreas de formación básica científica, desarrollo humano e investigación - Grefa Andi, Cecilia Jacinta (2016)
This research was conducted in order to identify the degree of authenticity of the evaluation of learning in the Bachelor of Science in Education at the Salesian University, Headquarters Quito, from content analysis of plans activities subjects in the area of Science, Human Development, Basic Training and Research during the period from March to September 2015. The study has a qualitative and quantitative approach, descriptive scope. Realism of activities, skills and relevance: data collection for the three principles of the theoretical foundation were considered. The results of the analysis of that information to visualize a trend of authenticity in the process of learning assessment; however, they remain some features of traditional assessment that authenticity is facing, particularly in relation to the realism of the tasks. The subject of learning assessment, helps us to understand, among others, the influence of cultural diversity in the learning process. As this issue of the assessment of learning, it enables us to understand the cultural diversity of the human being in the perception of knowledge. New knowledge and learning assessment methodological guide for teachers have the opportunity to strengthen and provide feedback to students who encounter difficulty in the respective subjects.